2020
DOI: 10.1007/s12008-020-00694-5
|View full text |Cite
|
Sign up to set email alerts
|

Fast interactive CFD evaluation of hemodynamics assisted by RBF mesh morphing and reduced order models: the case of aTAA modelling

Abstract: The medical digital twin is emerging as a viable opportunity to provide patient-specific information useful for treatment, prevention and surgical planning. A bottleneck toward its effective use when computational fluid dynamics (CFD) techniques and tools are adopted for the high fidelity prediction of blood flow, is the significant computing cost required. Reduced order models (ROM) looks to be a promising solution for facing the aforementioned limit. In fact, once ROM data processing is accomplished, the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 47 publications
(57 reference statements)
0
21
0
Order By: Relevance
“…Additionally, the FSI approach only partially accounts for the vessel movement caused by the heart contraction. To overcome the FSI limitations and to reduce the computation weight, more recently, CFD based on morphing with radial basis functions (RBF) ( 47 49 ) were proposed. Another point of discussion is given by the boundary conditions definition.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the FSI approach only partially accounts for the vessel movement caused by the heart contraction. To overcome the FSI limitations and to reduce the computation weight, more recently, CFD based on morphing with radial basis functions (RBF) ( 47 49 ) were proposed. Another point of discussion is given by the boundary conditions definition.…”
Section: Introductionmentioning
confidence: 99%
“… Compared pre-operative patient-specific simulation of the implant of a custom-made endograft prediction with post-operative outcomes. Numerical analyses; FEA Proof of concept; Precursor of a DT Biancolini et al 2020 Italy 52 High-fidelity surgical planning tool for thoracic aortic aneurysm repair to visualise, interactively and almost in real-time, the effect of various bulge shape parameters. ROM framework to overcome the computing costs required in CFD techniques that are needed for blood flow prediction.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, despite the time discrepancy, the CFD RBF can be considered affordable, as the physiological relevance increases considerably also considering that the mesh motion subroutine used in the simulation software are scripted and can be reused. Probably the routine be optimized even further, decreasing the additional computational effort even more to make more feasible the adoption of this technique in a clinical environment [72]. In summary, a comprehensive evaluation of a novel RBF mesh morphing technique demonstrated that morphing with CT gated dataset can be applied to study patient specific hemodynamics.…”
Section: Discussionmentioning
confidence: 99%